ZULKARNAIN PERSPEKTIF TAFSIR AL-QUR’AN DEPARTEMEN AGAMA RI ( KESEIMBANGAN AJARAN AGAMA DAN ILMU PENGETAHUAN ) - Ihsan, Wahyu (At-Tuhfah : Jurnal Studi Keislaman, 2022)
This study aims to analyze the history of Zulkarnain which the current generation needs to emulate because the figure of Zulkarnain can balance the teachings of religion and science. This study uses qualitative methods. There are two sources of data that will be used, namely primary data sources and secondary data sources. Primary data source, Interpretation of the Ministry of Religion of the Republic of Indonesia. and secondary data are books of thematic commentaries, tahlili interpretations and some literature on Zulkarnain's story, both from the perspective of commentators, philosophers, scientists and other scholars. The steps taken in this research are as follows. The first thing to do is to select a theme in the Qur'an (Zulkarnain's Story) then classify the background of the problem and the formulation of the problem. After that, collect the verses related to research (al-Kahf, juz 16 verses 83-99) and conduct a study of interpretation using the Tafsir of the Ministry of Religion of the Republic of Indonesia and other supporting literacy. The results of the study show that Zulkarnain is a pious figure in matters of hablu minallah, he has a humble nature, dares to carry out jihad, has high religious knowledge and is full of gratitude. In human relations, he has a fair, trustworthy, generous, giving and high knowledge nature.